Baicalein-corrected gut microbiota may underlie the amelioration of memory and cognitive deficits in APP/PS1 mice - Shi, Jing; Chen, Jie; Xie, Xinyun; Li, Yuanyuan; Ye, Wenjing; Yao, Jianbiao; Zhang, Xiangnan; Zhang, Tianyuan; Gao, Jianqing (Frontiers in Pharmacology, 2023)
Baicalein is an active ingredient extracted from the root of S. baicalensis Georgi, which exhibits cardiovascular protection, anti-inflammatory, and anti-microbial properties. Our previous study showed that chronic treatment of Baicalein ameliorated cognitive dysfunction in a mouse model of Alzheimer's disease (AD). However, it remains unknown whether Baicalein ameliorates cognitive deficits in AD mouse models by altering gut microbiota and its metabolites. Considering the important role of gut microbiota and its metabolites in AD, we used behavioral tests, metagenomic and untargeted metabolomics analyses to evaluate the effects of Baicalein on the APP/PS1 mice. Our research showed that treatment of Baicalein for two weeks ameliorated cognition and memory in a dose-dependent manner, as indicated by the significant increases in the Discrimination index and the Number of crossings and decrease in latency to the previous platform location in 8-month of age APP/PS1 mice in novel object recognition and water maze tests. The metagenomic analysis showed the abundance of the dominant phyla in all groups, including Bacteroidetes (14.59%-67.02%) and Firmicutes (20.19%–61.39%). LEfSe analysis of metagenomics identified three species such as s__Roseburia_sp_1XD42_69, s__Muribaculaceae_bacterium_Isolate_104_HZI, s__Muribaculaceae_bacterium_Isolate_110_HZI as Baicalein-treated potential biomarkers. Metabolite analysis revealed the increment of metabolites, including glutamate, thymine, and hexanoyl-CoA. Overall, the effects of Baicalein on memory and cognition may relate to the metabolism of nucleotides, lipids and glucose.